PEMBELAJARAN KONSEP TITIK DAN GARIS UNTUK MENGEMBANGKAN LITERASI MATEMATIKA SISWA SEKOLAH DASAR - Farah Azra Razita; Rella Widya Kenari; Yulia Saputri; Azamul Fadhly Noor Muhammad (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Learning the concepts of points and lines is an important foundation in elementary mathematics because it serves as the foundation for understanding geometry and space. This study aims to analyze the effectiveness of a learning model that emphasizes an understanding of the concepts of points and lines. The research method used was a literature review and descriptive analysis of various relevant sources, including textbooks, research articles, and observations of elementary school students' practices. The study results indicate that a constructivist-based learning approach, the use of concrete media, and visual exploration activities can improve students' abilities to identify, describe, and connect points and lines in contextual situations. Furthermore, the integration of simple problem-solving activities enables students to strengthen mathematical literacy, particularly in the aspects of reasoning, representation, and communication. Overall, this study strengthens and confirms that a learning strategy centered on understanding basic geometric concepts, especially points and lines, significantly improves elementary school students' mathematical literacy.